Respuesta :

x+3=(x+3)^2
x+3=(x+3)(x+3)
x+3= x^2+6x+9
x=x^2+6x+6
0=x^2+5x+6
0=(x+3)(x+2)
x=-2
x=-3

Answer:

x=-2 and x=-3  

Step-by-step explanation:

[tex]\sqrt{x+3} -4= x-1[/tex]

Solve the equation for x

Add 4 on both sides

[tex]\sqrt{x+3}= x+3[/tex]

Now take square on both sides

[tex]x+3= (x+3)^2[/tex]

[tex]x+3= (x+3)(x+3)[/tex]

[tex]x+3= x^2+6x+9[/tex]

[tex]x=x^2+6x+6[/tex]

[tex]0=x^2+5x+6[/tex]

[tex]0=(x+3)(x+2)[/tex]

x+3=0, x=-3

x+2=0, x=-2

LEts plug in -2 for x and verify the solution

[tex]\sqrt{x+3} -4= x-1[/tex]

[tex]\sqrt{-2+3} -4= -2-1[/tex]

[tex]\sqrt{1} -4=-3[/tex]

[tex]-3=-3[/tex]  True

Plug in x=-3

[tex]\sqrt{-3+3} -4= -3-1[/tex]

[tex]\sqrt{0} -4=-4[/tex]

[tex]-4=-4[/tex]  True

So x=-2 and x=-3 are the non extraneous solution